CD8 signaling in microglia/macrophage M1 polarization in a rat model of cerebral ischemia - Boddaert, Jan (PLoS One, 2018)
Classical or M1 activity of microglia/macrophages has been described in several neurodegenerative and brain inflammatory conditions and has also been linked to expansion of ischemic injury in post-stroke brain. While different pathways of M1 polarization have been suggested to occur in the post-stroke brain, the precise underlying mechanisms remain undefined. Using a transient middle cerebral artery occlusion (MCAO) rat model, we showed a progressive M2 to M1 polarization in the perilesional brain region with M1 cells becoming one of the dominant subsets by day 4 post-stroke. Comparing key receptors involved in M1 polarization (CD8, IFNγR, Clec4, FcγR, TLR3 and TLR4) and their signal transducers (Syk, Stat1, Irf3, and Traf6) at the day 4 time point, we showed a strong upregulation of CD8 along with SYK transducer in dissected perilesional brain tissue. We further showed that CD8 expression in the post-stroke brain was associated with activated (CD68+) macrophages and that progressive accumulation of CD8+CD68+ cells in the post-stroke brain coincided with increased iNOS (M1 marker) and reduced Arg1 (M2 marker) expression on these cells. In vitro ligand-based stimulation of the CD8 receptor caused increased iNOS expression and an enhanced capacity to phagocytose E. coli particles; and interestingly, CD8 stimulation was also able to repolarize IL4-treated M2 cells to an M1 phenotype. Our data suggest that increased CD8 signaling in the post-stroke brain is primarily associated with microglia/macrophages and can independently drive M1 polarization, and that modulation of CD8 signaling could be a potential target to limit secondary post-stroke brain damage.